Scaffolding recommendations for students’ essay planning - van Rijn, Lars; Wrede, Silke Elisabeth; de Witt, Claudia; Wang, Xia; Duong-Trung, Nghia; Jose, Angelin Mary; Pinkwart, Niels (Frontiers in Education, 2025)
Planning scientific essays is a fundamental activity for students to acquire and demonstrate research competence in higher education. The planning and writing process is complex and time-consuming, requiring significant effort from both students and tutors. Consequently, recommender systems have been used to support the writing process, but the evidence regarding their pedagogical effectiveness is sparse. In this study we conceptualize and evaluate an approach to closely align a recommender system with pedagogical principles of the specific use case. In our Wizard-of-Oz experiment we therefore used scaffolded recommendations to explore whether this approach can assist students in planning a scientific essay for a course in media education. The intervention resulted in positive effects on the time students’ need to be tutored for and the intention of students to reuse the system. We discuss implications of these results for the design of supporting essay planning through recommender systems, considering limitations of the method applied.